(untitled) (Revista Española de Fisiología, 1973)
After fractionation of wheat coleoptile segments, the specific activity of /? 1-3 gluca nase seems to be strongly bound to the cell wall, and can be partly released from it by a detergent. The glucanase activity increases in all fractions by the treatment of coleop tile segments with auxin. lAA-stimulation of /? 1-3 glucanase is reduced by 10 /ig/ml of cycloheximide. The possible relation between the cell wall bound glucanase and wall extension is discussed.